2020
DOI: 10.2337/dc20-1321
|View full text |Cite
|
Sign up to set email alerts
|

Has COVID-19 Delayed the Diagnosis and Worsened the Presentation of Type 1 Diabetes in Children?

Abstract: To evaluate whether the diagnosis of pediatric type 1 diabetes or its acute complications changed during the early phase of the coronavirus disease 2019 (COVID-19) pandemic in Italy. RESEARCH DESIGN AND METHODS This was a cross-sectional, Web-based survey of all Italian pediatric diabetes centers to collect diabetes, diabetic ketoacidosis (DKA), and COVID-19 data in patients presenting with new-onset or established type 1 diabetes between 20 February and 14 April in 2019 and 2020. RESULTS Fifty-three of 68 cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
127
3
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(151 citation statements)
references
References 12 publications
12
127
3
9
Order By: Relevance
“…In Germany, the frequency of DKA at diagnosis during COVID-19 was significantly higher compared with the two previous years (44.7% in 2020, 24.5% in 2019, and 24.1% in 2018), as well as the incidence of severe DKA (19.4% in 2020, 13.9% in 2019, and 12.3% in 2018) [63]. In Italy, a 23%-reduction in new T1D cases was observed concomitantly with an increase in the proportion of severe DKA (44.3% in 2020 vs 36.1% in 2019) [64].…”
Section: Communication As a Strategymentioning
confidence: 98%
See 1 more Smart Citation
“…In Germany, the frequency of DKA at diagnosis during COVID-19 was significantly higher compared with the two previous years (44.7% in 2020, 24.5% in 2019, and 24.1% in 2018), as well as the incidence of severe DKA (19.4% in 2020, 13.9% in 2019, and 12.3% in 2018) [63]. In Italy, a 23%-reduction in new T1D cases was observed concomitantly with an increase in the proportion of severe DKA (44.3% in 2020 vs 36.1% in 2019) [64].…”
Section: Communication As a Strategymentioning
confidence: 98%
“…Delays in information and education to specific groups during the pandemic led to risky behaviors, such as reluctance to visit healthcare centers even during emergencies [62]. Consequently, different authors reported higher frequency and/or severity of diabetic ketoacidosis (DKA) in individuals with newly diagnosed T1D during the pandemic [62,63,64]. In Germany, the frequency of DKA at diagnosis during COVID-19 was significantly higher compared with the two previous years (44.7% in 2020, 24.5% in 2019, and 24.1% in 2018), as well as the incidence of severe DKA (19.4% in 2020, 13.9% in 2019, and 12.3% in 2018) [63].…”
Section: Communication As a Strategymentioning
confidence: 99%
“…Diabetic ketoacidosis (DKA) is a severe acute complication of diabetes arising from a relative insulin deficiency, which occurs more often in children with type 1 diabetes (T1D) and in the setting of moderate to severe illness [1]. Recent studies found an increase in the rates of severe DKA in patients with newly diagnosed T1D during the severe acute respiratory coronavirus 2 (SARS-CoV-2) pandemic [2][3][4]. There have been no studies that examined the impact of the SARS-CoV-2 pandemic on DKA rates in emergency department (ED) patients with established T1D.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a review of the Spanish SARS-CoV-2 epicentre included cases of younger individuals [7] as compared to prior years, and, accordingly, our case involved a three-yearold boy. In fact, Italy recorded 44.3% of severe cases of DKA, compared to 36% during the same period in 2019 [8]. UK listed 70% of DKA cases, and approximately 52% were severe [9].…”
Section: Discussionmentioning
confidence: 96%